A GÊNESE E EVOLUÇÃO DO URBANISMO MODERNO E A PRODUÇÃO DA CIDADE: ALGUMAS REFLEXÕES - Costa, Lucemeire da Silva (Caminhos de Geografia, 2001)
This article boardes the appearance and the development of modern city planning, through a short historic view, pointing out the Capitalism decisive paper in the cities transformation. This evolution will be board, firstly, in an amplified view to, later, centralizes it in the Brazilian specific case. In this meaning, it’s presented the city planning ap pearance and development in the urban-industrial age, the Machine Age (1900-1940) commons urban landscapes, the currents and urban moviments in the XIX and XX centuries and the principals planning standards of measure adopt in the post war. In the Brazilian case, this study will be done through a historic periodization in four different moments, that identify the principal planning standards and recognize the social question teoric-politic circumstances and how the urban is represented in this model.